Evaluation of a multimedia youth anti-smoking and girls' empowerment campaign: SKY Girls Ghana - Paul Hutchinson; Alejandra Leyton; Dominique Meekers; Charles Stoecker; Francine Wood; Joanna Murray; Naa Dodua Dodoo; Adriana Biney (BMC, 2020)
Abstract Background Given the long-term health effects of smoking during adolescence and the substantial role that tobacco-related morbidity and mortality play in the global burden of disease, there is a worldwide need to design and implement effective youth-focused smoking prevention interventions. While smoking prevention interventions that focus on both social competence and social influence have been successful in preventing smoking uptake among adolescents in developed countries, their effectiveness in developing countries has not yet been clearly demonstrated. SKY Girls is a multimedia, empowerment and anti-smoking program aimed at 13-16-year old girls in Accra, Ghana. The program uses school and community-based events, a magazine, movies, a radio program, social media and other promotional activities to stimulate normative and behavioral change. Methods This study uses pre/post longitudinal data on 2625 girls collected from an interviewer-administered questionnaire. A quasi-experimental matched design was used, incorporating comparison cities with limited or no exposure to SKY Girls (Teshie, Kumasi and Sunyani). Fixed-effects modeling with inverse probability weighting was used to obtain doubly robust estimators and measure the causal influence of SKY Girls on a set of 15 outcome indicators. Results Results indicate that living and studying in the intervention city was associated with an 11.4 percentage point (pp) (95% CI [2.1, 20.7]) increase in the proportion of girls perceiving support outside their families; an 11.7 pp. decrease (95% CI [− 20.8, − 2.6]) in girls' perception of pressure to smoke cigarettes; a 12.3 pp. increase (95% CI [2.1, 20.7]) in the proportion of girls who had conversations with friends about smoking; an 11.7 pp. increase (95% CI [3.8, 20.8]) in their perceived ability to make choices about what they like and do not like, and 20.3 pp. (95% CI [− 28.4, − 12.2]) and 12.1 pp. (95% CI [− 20.7, − 3.5]) reductions in the proportion agreeing with the idea that peers can justify smoking shisha and cigarettes, respectively. An analysis of the dose-effect associations between exposure to multiple campaign components and desired outcomes was included and discussed. Conclusion The study demonstrates the effectiveness of a multimedia campaign to increase perceived support, empowerment and improve decision-making among adolescent girls in a developing country.